Evaluation of CGIAR Research Program on Maize - Gryseels, Guido; Betran, Javier; Chapman, Scott; Ketema, Seyfu; Sachdeva, Paramjit; Snapp, Sieglinde S. (CGIAR Independent Evaluation Arrangement, 2015)
The CGIAR Research Program on MAIZE (MAIZE) is led by CIMMYT and implemented in partnership with IITA and more than 300 other partners. It aims to double the productivity of maize-based farming systems, making them more resilient and sustainable and ultimately increasing farmers’ incomes and livelihoods. MAIZE’s main target group is smallholders who live in stress-prone environments and who have poor market access, which includes around 640 million people of which 72 million are maize dependent.